Perspektif Aksiologi terhadap Pendidikan Berkeadilan di Indonesia: Axiological Perspective on Equitable Education in Indonesia - Yeanny Suryadi; Dian Armanto; Wildansyah Lubis; Triayuni Triayuni (ITScience (Information Technology and Science), 2026)
Education is a strong pillar of a nation’s development towards genuine and equitable progress. Education is a pillar for building a strong nation, with character, able to adapt to the times while maintaining the nation’s noble culture, which serves as the foundation of its norms and characteristics. Hot issues in education continue to concern how the government contributes to the implementation of equitable and meaningful education, so that equitable development, in line with the discourse of ‘no one left behind’, can be achieved towards Indonesia Emas 2045. This study describes the extent to which the discourse of equitable education in Indonesia has been implemented from an axiological perspective. This research is a literature study. Data on equitable and inclusive education were collected from articles in academic databases, including Google Scholar, Taylor & Francis, and others. The results of this study indicate that, from an axiological perspective, the government’s efforts to uphold equitable education have been realised through various policies, implementation programs, and strategic initiatives oriented towards equity and inclusive education. Axiologically, equitable education aims to advance the discourse of equitable social welfare, building a virtuous society for all levels of Indonesian society across regions with diverse economic, geographic, and social backgrounds. Prudent steps have been taken with established goals, and existing obstacles and supports serve as the basis for further policy development.